STANDARD METHOD OF IMPLANT PLACEMENT. A RETROSPECTIVE STUDY OF THE SUCCESS RATE OF STANDART MID-SIZED IMPLANTS PLACED IN THE MANDIBLE, AT A PERIOD OF MORE THAN 7 YEARS POST IMPLANT PLACEMENT - Dumitru Sîrbu (Romanian Society of Oral Rehabilitation, 2018)
The present study is focused on the particularities of the standard implant placement protocol, emphasizing the results of the treatment in dynamics, evaluated according to the succes criteria established by Alrektsson et al. Aim of the study: Evaluation of implant-prosthetic rehabilitation results over time, by approaching the standard implant placement protocol. Material and Method: The retrospective and prospective study (2008-2017) included 110 patients (47 males and 63 females) aged 21-82 years old (mean age - 45,2 years old, SE ± 1,08, SD 11, 35), which addressed for implant-prosthetic rehabilitation. 404 dental implants were inserted into the mandible, in the alveolar ridge with sufficient bone supply, corresponding to type A, B + after Misch, with delayed insertion of the implants (type IV) and delayed functional load. Results: Average per patient - 3,7 implants. Average implant sizes: 4,0 mm in diameter and 12.0 mm in length. Resorption: 0,31 mm mesial and 0,32 mm distal at the stage of uncovering of the 319 implants; 0,74 mm mesial and 0,75 mm distal at 1 year of function, continuing with a nonessential resorption in the following years, stabilized around the depth of 1 mm at 5 years and more than 7 years. Conclusion: The conventional implantation protocol is predictable, with favorable results over time, with a high rate of implant success over a surveillance period of over 7 years.